PENGARUH BUDAYA ORGANISASI, KNOWLEDGE MANAGEMENT DAN LEADER MEMBER EXCHANGE TERHADAP KINERJA KARYAWAN DIVISI INFRASTRUKTUR 2 PT PEMBANGUNAN PERUMAHAN (PERSERO) TBK JAKARTA - I Wayan Wikananda Radina Artha; Syarifudin . (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the effect of organizational culture, knowledge management, leader member exchange on the employees performance of the Infrastructure 2 division of PT Housing Development (Persero) Tbk Jakarta.. This research uses quantitative methods with the analysis technique used, namely the Partial Least Square-Structural Equation Model (PLS-SEM) analysis. The sampling technique used is non-probability sampling and saturated sampling, with the number of respondents participating as many as 84 employees. Based on performance data from the Infrastructure 2 division of PT. Housing Development (Persero) Tbk Jakarta in 2019,2020 and 2021 there is a problem, namely experiencing a decline in performance. The results of the analysis show that there is a positive and significant relationship between organizational culture and knowledge management, organizational culture and leader member exchange, knowledge management and performance, leader member exchange and performance, as well as the relationship of organizational culture to performance through knowledge management and leader member exchange. From this research, it proves that the better and higher the implementation of organizational culture in knowledge management and leadership of member exchange leaders in the company, it will be followed by an increase in the performance of employees or companies in the Infrastructure division 2 of PT. Pembangunan Perumahan (Persero) Tbk Jakarta